THE INFLUENCE OF MUHAMMADIYAH ON NATIONAL EDUCATION POLICY: ANALYSIS OF CONTRIBUTIONS AND RECOMMENDATIONS - Armalena Armalena; Maigus Maigus; Syahrul Fadli; Julhadi Julhadi; Desi Asmaret (Journal International Inspire Education Technology, 2026)
Indonesian national education is the result of a continuous interaction between government policies and the contributions of civil society, including modern religious organizations such as Muhammadiyah, which has played a significant role in educational transformation since 1912. Amidst the demands of globalization and the need for an inclusive, adaptive, and character-based education system, it is important to understand Muhammadiyah’s influence in shaping the direction of national education policy. This study aims to identify the forms of this influence, including institutional contributions, advocacy roles, curriculum innovation, and strategic partnerships in supporting national education development. The Systematic Literature Review (SLR) method was used to systematically analyze 40 relevant accredited journal articles, resulting in a comprehensive thematic mapping. The results show that Muhammadiyah has a significant influence in four main aspects: expanding access to education through a broad and equitable network of institutions, contributing to policy advocacy involving Muhammadiyah figures and formal institutions, innovating in Islamic-based curriculum and pedagogy, and forming strategic partnerships with the government in equalizing and improving the quality of national education. Analysis of the distribution of articles shows that 35% focused on institutional contributions, 25% on policy advocacy, 20% on curriculum innovation, and 20% on forms of educational partnerships.